Combining environmental isotopes with Contaminants of Emerging Concern (CECs) to characterise wastewater derived impacts on groundwater quality. (1st September 2020) - McCance, W.; Jones, O.A.H.; Cendón, D.I.; Edwards, M.; Surapaneni, A.; Chadalavada, S.; Wang, S.; Currell, M.
Abstract: The potential for Wastewater Treatment Plants (WWTPs) to cause adverse impacts to groundwater quality is a major global environmental challenge. Robust and sensitive techniques are required to characterise these impacts, particularly in settings with multiple potential contaminant sources (e.g. agricultural vs. site-derived). Stable (δ 2 HH2O, δ 18 OH2O, δ 15 NNO3, δ 18 ONO3 and δ 13 CDIC ) and radioactive ( 3 H and 14 C) isotopes were used in conjunction with three Contaminants of Emerging Concern (CECs) - carbamazepine, simazine and sulfamethoxazole - to discriminate between multiple potential contamination sources at an Australian WWTP. The radioactive isotope tritium provided a sensitive indicator of recent (post-1990s) leakage, with groundwater activities between 0.68 and 1.83 TU, suggesting WWTP infrastructure (activities between 1.65 and 2.41) acted as a recharge 'window', inputting treated or partially treated effluent to the underlying groundwater system. This was corroborated by water stable isotopes, which showed clear demarcation between δ 18 OH2O and δ 2 HH2O in background groundwater (δ 18 OH2O and δ 2 HH2O values of approximately −5 and −28‰, respectively) and those associated with on-site wastewater (median δ 18 OH2O and δ 2 HH2O values of −1.2 and −7.6‰, respectively), with groundwater down-gradient of the plant plotting on a mixing line between these values. The CECs, particularly the carbamazepine:simazine ratio, provided a means to further distinguish wastewater impacts from other sources, with groundwater down-gradient of the plant reporting elevated ratios (median of 0.98) compared to those up-gradient (median of 0.11). Distinctive CEC ratios in impacted groundwater close to the WWTP (∼3.0) and further down-gradient (2.7–9.3) are interpreted to represent a change in composition over time (i.e., recent vs. legacy contamination), consistent with the site development timeline and possible changes in effluent composition resulting from infrastructure upgrades over time. The data indicate a complex set of co-mingled plumes, reflecting different inputs (in terms of both quantity and concentration) over time. Our approach provides a means to better characterise the nature and timing of wastewater derived impacts on groundwater systems, with significant global implications for site management, potentially allowing more targeted monitoring, management and remedial actions to be undertaken. Graphical abstract: Image 1 Highlights: Combined use of stable and radiogenic isotopes with CECs in groundwater. Accurate delineation of wastewater derived impacts as opposed to other sources. Insights into historic ('legacy') and recent contamination sources.